2001
DOI: 10.1042/bj3570321
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine synthetase expression alone is sufficient to induce l-asparaginase resistance in MOLT-4 human leukaemia cells

Abstract: Childhood acute lymphoblastic leukaemia (ALL) is treated by combination chemotherapy with a number of drugs, always including the enzyme l-asparaginase (ASNase). Although the initial remission rate is quite high, relapse and associated drug resistance are a significant problem. In vitro studies have demonstrated increased asparagine synthetase (AS) expression in ASNase-resistant cells, which has led to the hypothesis that elevated AS activity permits drug-resistant survival. The data presented show that not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
51
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 21 publications
6
51
0
Order By: Relevance
“…For example, in vitro studies with U937 cells demonstrated that ASNase-sensitive cells can be made resistant by persistent exposure to increasing levels of sublethal doses of the drug, and constitutive expression of ASNS in a human ALL cell line (MOLT-4) conferred ASNase-resistance onto sensitive parental cells. 14 Additional evidence has been provided from recent work by our group, which demonstrated that incubation of ASNase-resistant MOLT-4 cells with ASNase and the adenylated sulfoximine derivative 1 (Fig. 1) suppresses cell proliferation.…”
Section: Introductionmentioning
confidence: 71%
“…For example, in vitro studies with U937 cells demonstrated that ASNase-sensitive cells can be made resistant by persistent exposure to increasing levels of sublethal doses of the drug, and constitutive expression of ASNS in a human ALL cell line (MOLT-4) conferred ASNase-resistance onto sensitive parental cells. 14 Additional evidence has been provided from recent work by our group, which demonstrated that incubation of ASNase-resistant MOLT-4 cells with ASNase and the adenylated sulfoximine derivative 1 (Fig. 1) suppresses cell proliferation.…”
Section: Introductionmentioning
confidence: 71%
“…MOLT-4, a human T lymphoblastoid leukemia cell line, has been used extensively for studies of leukemia cell biology and anti-leukemia therapy (10,11). We have developed an MDR cell line MOLT-4/daunorubicin (DNR) from a T lymphoblastoid leukemia MOLT-4 cell line by exposing the parent cells to stepwise increasing concentrations of DNR over 3 months (12).…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally induced drug resistance in several leukaemic cell lines through the sequential escalation of drug dosage has provided insights into the underlying mechanisms of treatment failure (Beck, 1983; Den Boer et al , 1998; Sonneveld, 2000; Aslanian et al , 2001; Liu et al , 2002; Efferth et al , 2006; Munteanu et al , 2006). Nevertheless, only the CCRF‐CEM, MOLT‐4 and Jurkat T‐ALL cell lines have been developed to show drug resistance to anthracyclines, vinca alkaloids, glucocorticoids, or l ‐asparaginase ( l ‐asp).…”
mentioning
confidence: 99%